Aus der Geschichte der Deutschen Gesellschaft für Innere Medizin (DGIM) - Forsbach, Ralf; Hofer, Hans-Georg (DMW - Deutsche Medizinische Wochenschrift, 2018)
At the end of the 1960 s, the German Society for Internal Medicine faced a period of intensifying factional struggles. Traditional conservative views increasingly met with critics demanding reform efforts. These debates covered, among other things, the self-definition of the society, doctor-patient relationship, medical studies, hospital regulations, and the relationship between doctors and nursing staff. In 1972/73, these opposing opinions within the society became particularly obvious, when the former NS-Gaustudentenführer Gotthard Schettler, who felt strong resentments towards the members of the 1968 movement, was followed by the reform willing, politically left wing Herbert Begemann in the DGIM presidency. During his time in office, Begemann also focused on general political issues.
Keywords: Medizingeschichte; Deutsche Gesellschaft für Innere Medizin; 1968; Studentenbewegung; Ludwig Heilmeyer; Gotthard Schettler; Herbert Begemann